Analysis of Non Linear Frequency Modulation (NLFM) Waveforms for Pulse Compression Radar - Muhamad Ridwan Widyantara; Sugihartono -; Fiky Y. Suratman; Slamet Widodo; Pamungkas Daud (National Research and Innovation Agency, 2018)
Non Linear Frequency Modulation (NLFM) method can suppress the peak sidelobe level without additional windowing function. NLFM doesn’t require any weighting function because it has inbuilt one. NLFM has a variable frequency deviation function due to the relation between frequency and time of the signal which is not linear so that it is possible to suppress of peak sidelobe level. This paper studies the characteristic of various NLFM waveform, such as NLFM Tri Stage Piece Wise (TSPW), NLFM S, and NLFM Taylor. The study of Pulse Compression of NLFM waveform consists of three aspects. First, analysis of pulse compression performance. Second, analysis of background noise. Last, analysis of Doppler effects. The simulation is done using Matlab software. The lowest value Peak Sidelobe Level (PSL)of NLFM TSPW is about -20 dB while NLFM S and NLFM Taylor are about -32 dB and -39 dB. Additive White Gaussian Noise (AWGN) and Doppler Effect influenced the value of PSL for each NLFM waveform. NLFM Taylor has the best NLFM waveform when the Doppler Effect and AWGN cause the value of PSL become high. Comparison between NLFM Taylor and Linear Frequency Modulation(LFM) is done in radar surveillance applications to analyze the detectability performance where the condition of Radar Cross Section (RCS) for each target has different significant value. The three targets are commercial airplanes, helicopter and fighter. For detectability performance, NLFM Taylor can detect more clearly than LFM conventional.